2016
DOI: 10.1111/nph.14097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics and evolution of disease resistance in cereals

Abstract: Contents 320I.320II.321III.321IV.322V.324VI.328VII.329330References330 Summary Cereal crops produce a large part of the globally consumed food and feed. Because of the constant presence of devastating pathogens, the molecular characterization of disease resistance is a major research area and highly relevant for breeding. There has been recent and accelerating progress in the understanding of three distinct resistance mechanisms in cereals: resistance conferred by plasma membrane‐localized receptor proteins;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 104 publications
(161 reference statements)
1
92
0
3
Order By: Relevance
“…The plant immune system machinery is complex and is composed of two tiers of extracellular and intracellular receptors (Krattinger and Keller, ,b) that efficiently detect the presence of pathogens (for review, see Greeff et al ., ; Couto and Zipfel, ; Eckardt, ). In this study, we found a significant enrichment of signals of selection at genes involved in this first level of defense in the eastern population.…”
Section: Discussionmentioning
confidence: 99%
“…The plant immune system machinery is complex and is composed of two tiers of extracellular and intracellular receptors (Krattinger and Keller, ,b) that efficiently detect the presence of pathogens (for review, see Greeff et al ., ; Couto and Zipfel, ; Eckardt, ). In this study, we found a significant enrichment of signals of selection at genes involved in this first level of defense in the eastern population.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of NLR gene capture approaches promises to rapidly expand the repertoire of cloned rust-resistance genes [11]. To date, 9 wheat genes conferring resistance to leaf ( Lr1 , Lr21 , and Lr10 ), stem ( Sr22 , Sr33 , Sr35 , Sr45 , and Sr50 ), and stripe or yellow ( Yr10 ) rust pathogens have been cloned and all encode NLR receptor proteins [3, 11, 12]. The barley resistance to P .…”
Section: Race-specific Resistancementioning
confidence: 99%
“…As implied, non–race-specific resistance is defined as operating against all races of a pathogen species and is sometimes effective against multiple pathogens [3,12]. Such resistance is generally quantitative, involving a partial resistance phenotype in which the pathogen growth is slowed without an obvious immune response (Fig 1B).…”
Section: Non–race-specific and Multipathogen Resistancementioning
confidence: 99%
“…We have already mentioned genes within the STP transporter family like Lr67 . Additional genes include those encoding unusual kinases, receptor-like kinases (RLKs) and receptor-like proteins (RLPs) [69], and genes involving cell wall biosynthesis and metabolism, such as cysteine proteinase, phenylalanine ammonia-lyase, plasma membrane ATPase and chalcone synthase [58]. When a pathogen attacks its host, the first line of host defense is through secretion of cell surface pattern-recognition receptors (PRRs) and such defense-induced proteins may be recognized and overcome by specific pathogen effectors.…”
Section: Discussionmentioning
confidence: 99%